2021
DOI: 10.1186/s12931-020-01605-8
|View full text |Cite|
|
Sign up to set email alerts
|

Sputum ACE2, TMPRSS2 and FURIN gene expression in severe neutrophilic asthma

Abstract: Background Patients with severe asthma may have a greater risk of dying from COVID-19 disease. Angiotensin converting enzyme-2 (ACE2) and the enzyme proteases, transmembrane protease serine 2 (TMPRSS2) and FURIN, are needed for viral attachment and invasion into host cells. Methods We examined microarray mRNA expression of ACE2, TMPRSS2 and FURIN in sputum, bronchial brushing and bronchial biopsies of the European U-BIOPRED cohort. Clinical paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…However, ACE2 expression negatively and positively correlated with Th2- and Th17-dependent epithelial signatures, respectively. Contrasting results were obtained from a similar study in which the gene expression of ACE2, TMPRSS2 , and furin was elevated in severe asthma, particularly the neutrophilic phenotype, in comparison with mild-to-moderate asthma and healthy controls ( 51 ). Thus, there is a possibility that the neutrophilic phenotype in patients with severe asthma may place them at increased risk of COVID-19.…”
Section: Implications Of Asthma Pathobiology On Covid-19 Pathogenesiscontrasting
confidence: 74%
“…However, ACE2 expression negatively and positively correlated with Th2- and Th17-dependent epithelial signatures, respectively. Contrasting results were obtained from a similar study in which the gene expression of ACE2, TMPRSS2 , and furin was elevated in severe asthma, particularly the neutrophilic phenotype, in comparison with mild-to-moderate asthma and healthy controls ( 51 ). Thus, there is a possibility that the neutrophilic phenotype in patients with severe asthma may place them at increased risk of COVID-19.…”
Section: Implications Of Asthma Pathobiology On Covid-19 Pathogenesiscontrasting
confidence: 74%
“…Gender disparity in furin expression has been previously demonstrated in asthmatic patients. Specifically, bronchial cell samples obtained from asthmatic patients revealed that furin is positively associated with the male gender and this was speculated as a possible factor contributing to COVID-19 severity (96). Further analysis of genetic variations at the FCS and any associated gender differences may offer insight to the more pronounced COVID-19 severity and mortality in males.…”
Section: Furinmentioning
confidence: 99%
“…9 Sputum transcriptomics, SomaScan ® proteomics, and metagenomics were assayed as described previously. 5,6 Gene set variation analysis (GSVA) was performed to obtain the enrichment score (ES) of the endopeptidase genes (TMPRSS2 and furin). Spearman correlation coefficients were computed between endopeptidases ES and sputum inflammatory markers and metagenomics α-diversity measures.…”
Section: Association Of Endopeptidases Involved In Sars-cov-2 Infection With Microbial Aggravation In Sputum Of Severe Asthmamentioning
confidence: 99%
“…3 The heterogeneous inflammatory nature of asthma raises the possibility that the type of asthmatic inflammation might determine the outcome of SARS-CoV-2 infection in asthma. Type 2 (T2) inflammatory markers have been associated with decreased ACE2 expression in asthma 4,5 that could underlie the reduced risk of SARS-CoV-2 infection in asthmatics. In contrast, non-T2 asthma, particularly neutrophilic asthma, has been associated with higher ACE2 and endopeptidases (TMPRSS2 and furin) expression as compared with the T2-high phenotype 4,5 that might imply a worse outcome with COVID-19 infection.…”
Section: Association Of Endopeptidases Involved In Sars-cov-2 Infection With Microbial Aggravation In Sputum Of Severe Asthmamentioning
confidence: 99%
See 1 more Smart Citation